Students and Lecturers’ Perceptions of Pre-service Teachers’ Geography Education Competence Level and Influencing Factors in Five Initial Teacher Training Programs in the Southeast and Mekong Delta Regions of Vietnam - Ha, Thang Van (Vietnam Journal of Education, 2022)
Developing learners’ qualities and competence is the main orientation and central goal of the Vietnamese Education System in the current period. Therefore, quality teacher training plays an important role in achieving these goals. This study assessed the geography education competence level of pre-service teachers and the factors affecting them. This study adopted a quantitative approach. It was designed as a cross-sectional investigation in which 40 lecturers and 167 pre-service teachers at 5 initial teacher training programs/courses in Southern Vietnam were randomly sampled by the stratified random and simple sampling. The results indicated that there was a significant difference in the assessment of the student teachers’ competence by the two groups. Further, the strongest influencing factors on the development of the competences were learning facilities and students themselves. The study discussed the implications for faculty members and those involved in designing initial teacher education programs for students majoring in geography.